2011
DOI: 10.1002/ird.684
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Irrigation and Drainage Practices to Enhance Water Productivity and Reduce Pollution in a Rice Production System

Abstract: Water-saving irrigation and controlled drainage have been separately practised in many countries to increase water use efficiency and reduce non-point source pollution while maintaining crop yields. In a two-year field experiment in the Gaoyou Irrigation District of South China, water use, crop yield, and pollution loads were monitored in an integrated water-saving irrigation and controlled drainage (WSI-CD) system and an unregulated system. For both 2007 and 2008, irrigation water productivity (WP I ) and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…They also found that the loss of T-N and T-P decreased from 165.5 to 20.2 kg ha −1 for N and from 1.96 to 0.58 kg ha −1 for P by the reduction of irrigation. Peng et al (2012) also reported that water-saving irrigation (reduction of 20 to 40 % compared to the conventional irrigation) reduced loss of both N and P by around 35 %. Fig.…”
Section: Calculations and Statistical Analysesmentioning
confidence: 93%
“…They also found that the loss of T-N and T-P decreased from 165.5 to 20.2 kg ha −1 for N and from 1.96 to 0.58 kg ha −1 for P by the reduction of irrigation. Peng et al (2012) also reported that water-saving irrigation (reduction of 20 to 40 % compared to the conventional irrigation) reduced loss of both N and P by around 35 %. Fig.…”
Section: Calculations and Statistical Analysesmentioning
confidence: 93%
“…Since the 1990s, researchers have developed, tested and disseminated several water-saving irrigation techniques for rice cultivation, including controlled irrigation [40,41], intermittent irrigation [42,43], half-dry cultivation [44], filmed ground and dry cultivation [44], systems of alternate submergence-nonsubmergence [45] and alternate wetting and drying [46,47]. These methods share the absence of continuous standing water on the paddy field surface or soil moisture content lower than saturation; thus, the paddy field moisture conditions differ from those created by traditional flooding irrigation.…”
Section: Water Managementmentioning
confidence: 99%
“…Irrigation water is also over used; thus, most of the applied fertilizers is flushed out of the fields and causes eutrophication of downstream water bodies [41]. We can control the downstream water bodies, and let some aquatic plants absorb the nutrients in the drainage.…”
Section: Growing Rice With Low Agrochemicalsmentioning
confidence: 99%
“…The soil pH (1:5 with H 2 O) was 6.5, and the concentrations of organic carbon, total N, and total P were 18.1, 1.2, and 1.1 g kg −1 , respectively [28]. The water level was maintained at 5-7 cm above the soil surface in the rice crops before the late tillering stage, and then drained for the control of non-productive tillering [38]. After about one week, the paddy field was re-flooded, kept alternately wet and dry, and then drained again two weeks before rice harvest.…”
Section: Sample Collection and Analysismentioning
confidence: 99%